Calcul de la capacité anaérobie en course à pied et à vélo à l`aide de mesures post-exercices - Hill, D. W. (Science & Sports, 2023)
Objective Maximal accumulated oxygen deficit (MAOD) is a gold standard measure of anaerobic capacity. The purpose of this study was to evaluate an alternative measure that avoids the contentious assumptions and the time-consuming procedures of the MAOD method.